RANCANG BANGUN APLIKASI SISTEM PRESENSI SISWA BERBASIS ANDROD DENGAN FITURE QR CODE - M. Fahrizi Lutfiana (LPPM Institut Citra Buana Indonesia, 2026)
The manual attendance system currently implemented in many schools is inefficient and prone to fraud, requiring digital transformation to improve the accuracy and transparency of student attendance data. This study aims to design and build a QR Code-based student attendance system accessible via mobile devices to replace conventional attendance recording. This study uses the waterfall system development method, consisting of requirements analysis, design, implementation, and testing phases. The application was developed using the Flutter, with system feasibility testing utilizing the Black Box Testing method involving main functional scenarios. The test results show that all application functionalities run perfectly without functional obstacles, where the system is able to record QR Code scans automatically, match student identities, and save them directly into a centralized database. In conclusion, this QR Code-based attendance system has proven effective in cutting administrative recording time, minimizing data recapitulation errors, and disciplining students through accurate recording.